Five On Finniston Farm - Enid Blyton
Julian, Dick, Anne, George and Timmy the dog find excitement and adventure wherever they go in Enid Blyton's most popular series. In book eighteen, the Famous Five hunt for the lost dungeons of a ruined castle on Finniston Farm. The friends are determined to find them, and whatever they hide, but they are not alone. Can the Famous Five get there first? The text in this edition has been sensitively edited for today's reader and is unillustrated.